Introducing the White Noise task in childhood: associations between speech illusions and psychosis vulnerability. Issue 13 (22nd July 2016) - Rimvall, M. K.; Clemmensen, L.; Munkholm, A.; Rask, C. U.; Larsen, J. T.; Skovgaard, A. M.; Simons, C. J. P.; van Os, J.; Jeppesen, P.
Abstract : Background: Auditory verbal hallucinations (AVH) are common during development and may arise due to dysregulation in top-down processing of sensory input. This study was designed to examine the frequency and correlates of speech illusions measured using the White Noise (WN) task in children from the general population. Associations between speech illusions and putative risk factors for psychotic disorder and negative affect were examined. Method: A total of 1486 children aged 11–12 years of the Copenhagen Child Cohort 2000 were examined with the WN task. Psychotic experiences and negative affect were determined using the Kiddie-SADS-PL. Register data described family history of mental disorders. Exaggerated Theory of Mind functioning (hyper-ToM) was measured by the ToM Storybook Frederik. Results: A total of 145 (10%) children experienced speech illusions (hearing speech in the absence of speech stimuli), of which 102 (70%) experienced illusions perceived by the child as positive or negative (affectively salient). Experiencing hallucinations during the last month was associated with affectively salient speech illusions in the WN task [general cognitive ability: adjusted odds ratio (aOR) 2.01, 95% confidence interval (CI) 1.03–3.93]. Negative affect, both last month and lifetime, was also associated with affectively salient speech illusions (aOR 2.01, 95% CI 1.05–3.83 and aOR 1.79, 95% CI 1.11–2.89, respectively). Speech illusions were not associated with delusions, hyper-ToM or family history of mental disorders. Conclusions: Speech illusions were elicited in typically developing children in a WN-test paradigm, and point to an affective pathway to AVH mediated by dysregulation in top-down processing of sensory input.